2015
DOI: 10.1089/apc.2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Barriers and Facilitators of Access to HIV Testing Among Men Who Have Sex with Men in China

Abstract: Diagnosis of HIV is the entry point into the continuum of HIV care; a well-recognized necessary condition for the ultimate prevention of onward transmission. In China, HIV testing rates among men who have sex with men (MSM) are low compared to other high risk subgroups, yet experiences with HIV testing among MSM in China are not well understood. To address this gap and prepare for intervention development to promote HIV testing and rapid linkage to treatment, six focus groups (FGs) were conducted with MSM in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…Successful experiences have demonstrated the benefits of self-testing, such as time/location convenience, protection against privacy disclosure, and increased HIV testing frequency. 28,29,56,57 Innovative testing provisions, such as the community-initiated home-based counseling and self-testing, should be expanded to see whether they can succeed in involving more Chinese MSM to periodically test for HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful experiences have demonstrated the benefits of self-testing, such as time/location convenience, protection against privacy disclosure, and increased HIV testing frequency. 28,29,56,57 Innovative testing provisions, such as the community-initiated home-based counseling and self-testing, should be expanded to see whether they can succeed in involving more Chinese MSM to periodically test for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous studies also suggested some key barriers resulting in suboptimal HIV testing experience among Chinese MSM, such as low perception of HIV risk, inconvenient clinic time/location, HIV stigma/discrimination, name-based testing policy to potentially harm confidentiality, lack of professionalism and low quality in HIV testing service provision. 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…Details of the study design have been described elsewhere. 27 In short, the Chaoyang Chinese AIDS Volunteer Group (CCAVG), a community-based gay-friendly organization in Beijing, recruited eligible participants. We used a peer-referral snowball recruitment strategy to engage additional participants.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…10 For those not on ART, they are eligible to receive one free CD4 and HIV viral load test each year, but patients have to pay for additional tests. 17 It is worth mentioning that when this policy was established, MSM did not largely represent in the HIV epidemic, and therefore did not receive adequate attention from the government commensurate with its focus on other key populations (e.g., former plasma donors, PWID, FSW). [17][18][19][20][21] Hence, MSMfriendly programs were late in development, often without a clear risk reduction strategy and HIV-related service provision policy.…”
Section: Introductionmentioning
confidence: 99%
“…By 2013, MSM accounted for 21.3 % of all people living with HIV/AIDS (PLWHA) in China [2], and their HIV prevalence increased from 3.0 % in 2006, to 7.6 % in 2013 [2]. Although many HIV prevention intervention programs highlight Chinese MSM as a key population, MSM are documented to continue with a high prevalence of risky behaviors, such as condomless anal sex, substance abuse, multiple sexual partnership and lack of routine HIV testing [3][4][5][6][7]. Hence, continued HIV transmission occurs within and beyond this population through both homosexual and heterosexual contacts [8].…”
Section: Introductionmentioning
confidence: 99%